The Modulation of Water, Nitrogen, and Phosphorous Supply for Growth Optimization of the Evergreen Shrubs Ammopiptanthus mongolicus for Revegetation Purpose - Roy, Rana; Mahboob, M. Golam; Arena, Carmen; Kader, Md. Abdul; Sultana, Shirin; Hasan, Ahmed Khairul; Wang, Jinxin; Sarker, Tanwne; Zhang, Ruiqi; Barmon, Milon (Frontiers in Plant Science, 2021)
Surface mining is a critical anthropogenic activity that significantly alters the ecosystem. Revegetation practices are largely utilized to compensate for these detrimental impacts of surface mining. In this study, we investigated the effects of five water (W) regimes [W40: 40%, W48: 48%, W60: 60%, W72: 72%, and W80: 80% of field capacity (FC)], five nitrogen (N) (N0: 0, N24: 24, N60: 60, N96: 96, and N120: 120 mg kg−1 soil), and five phosphorus (P) fertilizer doses (P0: 0, P36: 36, P90: 90, P144: 144, and P180: 180 mg kg−1 soil) on morpho-physiological and biochemical parameters of Ammopiptanthus mongolicus plants to assess the capability of this species to be used for restoration purposes. The results showed that under low W-N resources, A. mongolicus exhibited poor growth performance (i.e., reduced plant height, stem diameter, and dry biomass) in coal-degraded spoils, indicating that A. mongolicus exhibited successful adaptive mechanisms by reducing its biomass production to survive long in environmental stress conditions. Compared with control, moderate to high W and N-P application rates greatly enhanced the net photosynthesis rates, transpiration rates, water-use efficiency, chlorophyll (Chl) a, Chl b, total Chl, and carotenoid contents. Under low-W content, the N-P fertilization enhanced the contents of proline and soluble sugar, as well as the activities of superoxide dismutase, catalase, and peroxidase in leaf tissues, reducing the oxidative stress. Changes in plant growth and metabolism in W-shortage conditions supplied with N-P fertilization may be an adaptive strategy that is essential for its conservation and restoration in the desert ecosystem. The best growth performance was observed in plants under W supplements corresponding to 70% of FC and N and P doses of 33 and 36 mg kg−1 soil, respectively. Our results provide useful information for revegetation and ecological restoration in coal-degraded and arid-degraded lands in the world using endangered species A. mongolicus.